If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4=r/5-3
We move all terms to the left:
4-(r/5-3)=0
We get rid of parentheses
-r/5+3+4=0
We multiply all the terms by the denominator
-r+3*5+4*5=0
We add all the numbers together, and all the variables
-1r+35=0
We move all terms containing r to the left, all other terms to the right
-r=-35
r=-35/-1
r=+35
| 8f-14=42 | | -5k=-5.65 | | 37=3v-38 | | 49/v=7 | | 5q-14=51 | | 63=15+4z | | 8-4/5p=32 | | 9z-18=72 | | –4g+5=–9g | | 3n=-99 | | 46/u=6 | | 110=-19/2(x-0) | | 36/v=6 | | 3x+86=44+2x | | -5t+13=-12 | | 45/u=3 | | 6(11r=10)=192 | | q+27/7=10 | | -12=-4+b | | 7(c+9)=84 | | -15=½(x+6) | | 7(h+52)=-14 | | 8.7x=5.7 | | 9(z3)=45 | | 4(n−3)+2n=12 | | 8u+4=92 | | 6v+15=-3 | | p+23/8=7 | | 9(z+3=45 | | 3y+3=17 | | 9=25-4d | | 9(z+30=45 |